Binding of von Willebrand Factor to Complement C1q Decreases the Phagocytosis of Cholesterol Crystals and Subsequent IL-1 Secretion in Macrophages - Donat, Claudia; Thanei, Sophia; Trendelenburg, Marten (Frontiers in Immunology, 2019)
Complement C1q, the initiation molecule of the classical pathway, exerts various immunomodulatory functions independent of complement activation. Non-classical functions of C1q include the clearance of apoptotic cells and cholesterol crystals (CC), as well as the modulation of cytokine secretion by immune cells such as macrophages. Moreover, C1q has been shown to act as a binding partner for von Willebrand factor (vWF), initiation molecule of primary hemostasis. However, the consequences of this C1q-vWF interaction on the phagocytosis of CC by macrophages has remained elusive until now. Here, we used CC-C1q-vWF complexes to study immunological effects on human monocyte-derived macrophages (HMDMs). HMDMs were investigated by analyzing surface receptor expression, phagocytosis of CC complexes, cytokine secretion and caspase-1 activity. We found that vWF only bound to CC in a C1q-dependent manner. Exposure of macrophages to CC-C1q-vWF complexes resulted in an upregulated expression of phagocytosis-mediating receptors MerTK, LRP-1 and SR-A1 as well as CD14, LAIR1 and PD-L1 when compared to CC-C1q without vWF, whereas phagocytosis of CC-C1q complexes was hampered in the presence of vWF. In addition, we observed a diminished caspase-1 activation and subsequent reduction in pro-inflammatory IL-1 cytokine secretion, IL-1/IL-1RA ratio and IL-1/IL-1RA ratio. In conclusion, our results demonstrate that vWF binding to C1q substantially modulates the effects of C1q on HMDMs. In this way, the C1q-vWF interaction might be beneficial in dampening inflammation, e.g. in the context of atherosclerosis.